2023
DOI: 10.1182/blood.2023020078
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and classification of myelodysplastic syndromes

Robert P. Hasserjian,
Ulrich Germing,
Luca Malcovati

Abstract: Myelodysplastic syndromes (MDSs) are neoplastic myeloid proliferations characterized by ineffective hematopoiesis resulting in peripheral blood cytopenias. MDS is distinguished from non-neoplastic clonal myeloid proliferations by the presence of morphologic dysplasia and from acute myeloid leukemia (AML) by a blast threshold of 20%. The diagnosis of MDS can be challenging due to the myriad other causes of cytopenias: accurate diagnosis requires the integration of clinical features with bone marrow and peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…MDS diagnosis traditionally relies on clinical and morphologic characterization, as well as genetic criteria [29,30]. The recognition of dysplastic features is crucial for MDS diagnosis, with the recommended threshold for dysplasia set at 10% for all lineages [2].…”
Section: Diagnosis and Classificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…MDS diagnosis traditionally relies on clinical and morphologic characterization, as well as genetic criteria [29,30]. The recognition of dysplastic features is crucial for MDS diagnosis, with the recommended threshold for dysplasia set at 10% for all lineages [2].…”
Section: Diagnosis and Classificationsmentioning
confidence: 99%
“…In this regard, CD34, CD117, CD33, myeloperoxidase, and lysozyme staining can assist in quantifying myeloid blasts [33]. In addition, a useful accuracy in blast counting, other than valuable findings on the pathological immunophenotype features of MDS cell populations, can be provided by multiparametric flow cytometry (MFC), although this methodology has still only a complementary role [29] in this field and it is not yet widely used in MDS diagnosis [41]. Although cytogenetic analysis maintains a fundamental role in the diagnosis and especially prognosis of MDS patients [35,36], with about half of them carrying one karyotype alteration [4,34], recent genomic advances have provided remarkable improvement in this setting [5,42].…”
Section: Diagnosis and Classificationsmentioning
confidence: 99%
“…S14 ). When clonality is detected in PB, current guidelines recommend a BM examination for diagnosing a myeloid neoplasm [ 9 ] and assessing prognostic scores [ 10 ]. BM examination at diagnosis might be replaced in the future by PB monitoring in certain clinical settings (e.g., small/stable clone, low-risk mutation like sole DNMT3A [ 11 ], no therapeutic indication) [ 12 14 ].…”
Section: To the Editormentioning
confidence: 99%
“…For example, the assessment of minimal residual disease (MRD) has increasingly become a cornerstone of the clinical management of haematological malignancies. Myeloid cell immunophenotyping is an important tool for the diagnosis of myeloid dysplasia in MDS [ 18 ], which can be accompanied by a variety of myeloid cell immunophenotypic abnormalities characterised by abnormal granulocyte CD13/CD16 phenotypes, abnormal expression of CD56 by monocytes and decreased expression of CD71 by erythrocytes [ 19 , 20 ]. It has been shown that monocytes in patients with MPN abnormally express CD56 and have an increase in intermediate and non-classical monocytes [ 21 ], furthermore, granulocytes in patients with PMF also show abnormal features such as an abnormal CD13/CD16 phenotype and expression of CD56 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%